2022
DOI: 10.1002/jso.26876
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to apixaban for extended thromboprophylaxis after major abdominal or pelvic surgery for cancer: A prospective cohort study

Abstract: Background: Due to lack of data, direct oral anticoagulants are not considered by guidelines for venous thromboembolism (VTE) prophylaxis after cancer surgery.Adherence to low-molecular-weight heparin injections in this setting is sometimes poor.Aim: Analysis of adherence to oral apixaban for extended thromboprophylaxis.Methods: Consecutive patients discharged after major surgery for abdominal/pelvic cancer and considered eligible for extended prophylaxis were offered apixaban 2.5 mg twice daily. Primary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…While we did not evaluate barriers to prescription, studies have reported lack of insurance, inability to afford medication, and requiring additional insurance authorization as significant hurdles 20 . Patient adherence, especially around performing self‐injections, are another source of concern among prescribing providers 20 . Further studies should look to understand barriers specific to the Medicare population and to understand patient and provider perspectives that limit extended VTE prophylaxis despite the reported benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we did not evaluate barriers to prescription, studies have reported lack of insurance, inability to afford medication, and requiring additional insurance authorization as significant hurdles 20 . Patient adherence, especially around performing self‐injections, are another source of concern among prescribing providers 20 . Further studies should look to understand barriers specific to the Medicare population and to understand patient and provider perspectives that limit extended VTE prophylaxis despite the reported benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlight the need for addressing patient and provider‐specific barriers that impede extended VTE prophylaxis prescription. While we did not evaluate barriers to prescription, studies have reported lack of insurance, inability to afford medication, and requiring additional insurance authorization as significant hurdles 20 . Patient adherence, especially around performing self‐injections, are another source of concern among prescribing providers 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to DOACs perioperatively and patient satisfaction are rated higher of oral anticoagulants compared to SC low molecular weight heparin. 11 When comparing apixaban to low molecular weight heparin for postoperative prophylaxis, patient satisfaction was significantly greater in the apixaban group with regard to ease of administration and pain associated with the medication which, aiming for a patient -centered practice, is highly desirable for a patient recovering from major surgery. 8 Although DOACs are becoming increasingly desirable as evidence-based alternative in oncologic surgery thrombosis prevention, this task is still undone.…”
mentioning
confidence: 99%